IMPROVING DIGITAL LITERACY OF VILLAGE OFFICIALS TO CREATE SMART VILLAGES AND IMPACTFUL PUBLIC SERVICES - Sunaryanto; Eny Haryati; Sapto Pramono (International Journal of Multidisciplinary Reseach, 2026)
Unequal data security and digital literacy among village officials are major obstacles to the digitalization of public services at the village level. This study aims to analyze the digital literacy of village officials and examine its relationship with technology acceptance and the implementation of impactful public services towards a smart village. The study used a mixed methods approach with a sequential explanatory design. The study population was village officials in Blitar Regency, East Java; a quantitative sample of 80 officials from eight villages, supplemented by 14 qualitative informants. Quantitative data were collected through a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), a statistical technique for testing relationships between variables; qualitative data were analyzed thematically and integrated to explain quantitative findings. Descriptive results show the highest perception of technology usefulness (average 4.06), while digital security was the lowest (2.96). PLS-SEM results prove that digital literacy has a positive and significant effect on perceived ease of use (β=0.639) and perceived usefulness (β=0.547). Both encourage system use, which subsequently has a strong influence on impactful public services (β=0.614). However, perceived ease of use did not significantly influence perceived usefulness. This finding confirms that human capabilities, not simply the availability of technology, determine the quality of digital services. The study concludes that strengthening digital literacy is a strategic lever for realizing smart villages and impactful public services, which requires support from tiered training, data security standards, and inclusive mentoring.